The Effects of Anxiety on Balance Parameters in Young Female University Students - Abbas Rahimi; Zahra Ebrahim Abadi (Iranian Journal of Psychiatry, 2012)
Objective: In human beings, the balance control is a result of an integration of physical and psychological factors and people show different reactions when feel anxious or face stability threatened conditions such as standing on an unstable surface. University students, particularly the female ones, are a group of the society who are prone to face anxieties. The current study focused on the effects of anxiety on balance index in young female university students.Methods: A group of 15 female students with a high anxiety score (higher than 42 in Shpielberger Questionnaire) and a group of 15 female students with a low anxiety score (lower than 42 in Shpielberger Questionnaire) were recruited for this study. Using a Biodex stabilometer (Biodex System, USA), the antero-posterior (AP), medio-latral (ML) and the overall dynamic stability index (SI) of the subjects were recorded and compared.Results: The results revealed a significant difference between the two groups. Subjects with a high anxiety score showed a stability index higher than those in the low anxiety group (p<0.005), which simply indicate significantly less stability in this group.Conclusion: This study showed that subjects with higher anxiety scores were less stable compared to those subjects with lower anxiety scores.